Analysis of Data on the Evolution of the Dislocation Structure of Nanostructured Zirconium Obtained by the Low-temperature Acoustic Technique - P. P. Pal-Val; A. P. Rybalko; L. N. Pal-Val; E. N. Vatazhuk (Newest Updates in Physical Science Research Vol. 1, 2021)
The temperature dependences of acoustic properties of nanostructured and polycrystalline zirconium are investigated in the temperature range 100 - 340 K. The effect of severe plastic deformation and subsequent annealing on key parameters of the Koiwa-Hasiguti acoustic relaxation in zirconium is studied in detail. It is established that due to intensive plastic deformation the relaxation strength considerably increases and the temperature and the width of the corresponding relaxation peak systematically decrease with reduction of the mean grain size in the samples. Annealing leads to a partial recovery of the relaxation strength and the peak temperature back to the initial values in undeformed samples but the width of the relaxation peak shows an additional decrease. The majority of the effects observed can be explained by changes in dislocation subsystems of the samples during intensive plastic deformation and annealing. An influence of a random scatter of the relaxation time on the main parameters of the Koiwa-Hasiguti peak is established using the statistical analysis based on the lognormal distribution. It is shown, that the parameter b of the lognormal distribution determines the width, height and asymmetry of the peak and also allows estimating the relaxation strength from the peak height. An algorithm of retrieving of the parameter b from experimental data is presented.